Influence of vicasol on the condition of periodntal tissues under the modeling of periodontitis - Savelieva, N.; Schneider, S.; Tkachenko, E. (My University, 2020)
Vikasol in experiments on 22 white rats in the tissues of the oral cavity showed periodontoprotective, antioxidant, antiinflammatory properties in terms of periodontitis modeling. He increased the content of hydroxyproline in the gums and glycosaminoglycans in periodontal tissues.
Keywords: vikasol; model of periodontitis; lipid peroxidation; antioxidant enzymes; hydroxyproline; glycosaminoglycans